2008
DOI: 10.1007/s11250-008-9259-6
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of dairy cattle systems in an irrigated perimeter and in a suburban region: case study from Morocco

Abstract: Multivariate analyses were used to compare dairy production practices and their consequences on milk yield and profitability in cattle farms from two representative regions of Morocco. A regular follow-up of 118 farms (48 in the Rabat-Salé suburban belt and 70 in the Gharb irrigated perimeter) was undertaken to obtain accurate data. Results show significant differences between the two regions. Intensive milk production was more frequent in the suburban zone (more concentrates and better annual milk yield per c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
1
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 18 publications
2
5
1
1
Order By: Relevance
“…This agrees with previous research in Morocco (Sraïri et al, 2009a) and other countries (Armstrong, 2004;Sultana et al, 2014). High variability among farms was observed, reflecting differences resulting from on-farm practices in all production functions, from water to cattle products.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This agrees with previous research in Morocco (Sraïri et al, 2009a) and other countries (Armstrong, 2004;Sultana et al, 2014). High variability among farms was observed, reflecting differences resulting from on-farm practices in all production functions, from water to cattle products.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, its water requirements are mainly fulfilled from rainfall. Lucerne DM yield reached an average of 9190 kg/ha, which is higher than the results of a previous study (6820 kg of DM/ha) conducted in a semi-arid irrigation scheme in Morocco (Sraïri et al, 2009a). The differences may be explained by higher rainfall in the current study (451 v. 210 mm).…”
Section: Discussioncontrasting
confidence: 86%
See 1 more Smart Citation
“…Indeed, these farms have specific characteristics that ensure their efficiency and resilience against milk market volatility such as their dualpurpose breeding practices and low labour costs (Sraïri et al 2009a). Dairy production provides them with a good income opportunity, but their limited land resources, especially in irrigated perimeters, mean they do not have enough fodder and consequently feed their cows imbalanced dietary rations which have a negative impact on milk yield and profitability (Sraïri et al 2009b). Increasing their milk production to respond to market demand should be based on improving milk yield per cow rather than increasing the cow stocking rate at farm level, which is already quite high (MADR 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Such a structure implies a relatively high number of farms with cattle (respectively 212,000; 720,000 and 112,000 in Algeria, Morocco and Tunisia), with marked differences in their production characteristics: genetic type of cattle, feeding systems, respective weight of meat and milk in the production strategies, etc. Attempts to establish typologies of farms on their functioning characteristics have revealed that variables such as the efficiency of feed resources conversion to milk, the level of dairy intensification (mainly milk yield per lactating cow) and the economic profitability are the most decisive, with no effect of farms geographic location (whether in an irrigated scheme or a rain fed suburban region) (Sraïri et al 2009b). Therefore, cattle’s feeding represents an important constraint in this region and has significant consequences on farms’ performances.…”
Section: Introductionmentioning
confidence: 99%